ADOLESCENTS’ INVOLVEMENT IN SOCIAL MEDIA: BEFORE AND DURING COVID-19 PANDEMIC - Hudimova, Alisar (International Journal of Innovative Technologies in Social Science, 2021)
Social media are an indispensable modern adolescents’ daily ritual. The present study investigates the specifics of social media influence on the adolescents’ psychological wellbeing in everyday life and during Covid-19. The research hypothesis stated that excessive social media use could provide loneliness, depression, and lack of sleep. The investigation is based on data received from interviews, questionnaires, and statistical analysis. A group of 516 psychology and medical students (78.8% females, 21.2% males) aged 15-21 took part in the study via Google Form survey conducted in Odesa I.I. Mechnikov National University, Ukraine. The participants’ overall well-being, loneliness, level of stress were assessed in correlation with personality characteristics and tendency to social media disorder. The obtained results showed that the more time adolescents spend on social media, the more real-life relationships decrease due to online isolation in social terms. The predictors of social media disorder are difficulties in relationships with family, time spent on social media and psycho-emotional background. It is determined that the social media use creates the illusion of participation and importance for a large circle of people. The study provides evidence that the unsatisfactory level of modern adolescents’ well-being can be explained by the passive use of social media, which provokes emotional lability, irritability, depression, and sleep deprivation.